Fe3O4/g‐C3N4 Nanozyme for Production of L‐DOPA as Mimetics of Tyrosine Hydroxylase. Issue 2 (3rd November 2022) - Shang, Qi; Zhang, Ling; Chen, Chan; Tang, Weikang; Han, Mengqi; Chen, Qinfei; Liu, Wenbin
Abstract: L‐DOPA is in large demand as the mainstay of therapeutic treatment for Parkinson's disease. The development of a facile route is urgently required for production of L‐DOPA. A nanozyme was developed for biomimetic synthesis of L‐DOPA by mimicking natural tyrosine hydroxylase. Fe3 O4 /g‐C3 N4 nanocomposite was fabricated by introducing iron oxide into g‐C3 N4 nanosheets. Formation of Fe−N bonds with structure resembled the active center. The nanozyme possessed superparamagnetic characteristics and wide light response range. The nanozyme exhibited similar activity as tyrosine hydroxylase by catalyzing hydroxylation of tyrosine in the presence of visible light irradiation and hydrogen peroxide. Maximum yield and titer was obtained as 15% and 1 mM for production of L‐DOPA, respectively. The nanozyme demonstrated high stability and reusability. The nanozyme catalyzed the reaction in an analogous mechanism with Fe IV O 2+ as the dominant active species. It might provide a promising insight to produce L‐DOPA due to advantages of easy separation and mild conditions. Abstract : A nanozyme was developed for biomimetic synthesis of L‐DOPA through selective hydroxylation of tyrosine by mimicking natural tyrosine hydroxylase with resemblance on structure, activity, and mechanism. It demonstrated magnetic recoverability and high reusability. Mild reaction condition and environment friendly process was achieved.